Analysis of 4 Cases of Left Bundle Branch Block With Ventricular Preexcitation - M. M. Li Yi; B. M. Li Xingjie (Annals of Noninvasive Electrocardiology, 2025)
ABSTRACT This paper reports 4 cases of ventricular preexcitation (WPW) accompanied by left bundle branch block (LBBB). WPW appeared intermittently in all cases: Case 1 involved a right‐sided accessory pathway, while Cases 2–4 involved left‐sided accessory pathways. The electrocardiographic characteristics of both right‐sided and left‐sided accessory pathways coexisting with LBBB are discussed.